Calm : 50 mindfulness exercises to de-stress wherever you are - Unger, Arlene K. (London : White Lion Publishing, 2020)
Featuring 50 easy-to-follow mindfulness, EBT and CBT exercises to combat stress, this little book provides an antidote to the clamour and strain of everyday living. The perfect size to keep in a handbag or pocket, it has been designed as a tool to keep close by and turn to in a busy day.
Originally published: London: Apple, 2015.
Keywords: Mindfulness (Psychology); Meditation; Calmness; Relaxation -- Technique; Religion